Institutional quality impacts on the offer size of IPOs in the Hong Kong market - Jingyu, Wu (2019)
The major purpose of the present study is to examine how the institutional quality impact on the offer size of initial public offering (IPO) listed on the Main Board of Hong Kong Stock Exchange during the year 2000 to 2017. This study utilizes three control variables for controlling the significance between institutional quality and offer size. Few empirical pieces of evidence measure the relationship between institutional quality and offer size. Therefore, this study fills the gap of literature on the significance of institutional quality on the offer size. There are six dimensions of institutional quality utilized from World Governance Indicators (WGI) that including government effectiveness, rule of law, control of corruption, political stability, voice and accountability and regulatory quality. The agency theory and signaling theory are used to further explain the impacts of institutional quality on the offer size. The present study utilizes the cross-sectional multi regression analysis to examine the hypothesis. Based on the analysis of the data of 1042 IPOs in Hong Kong, the result of this study shows that government effectiveness and regulatory quality negatively impact the offer size, and rule of law, control of corruption, political stability and voice and accountability positively impact on the offer size. Besides, the interest rate and the stock market return reflect a positive significance with offer size, but the Gross Domestic Price (GDP) growth shows a negative relationship with offer size. The significance of the present study may remind the regulators to improve the institutional quality to promote the growth of the market.